Electroacupuncture Combined With Diet Treatment Has a Therapeutic Effect on Perimenopausal Patients With Abdominal Obesity by Improving the Community Structure of Intestinal Flora - Sheng, Jili; Yang, Geyao; Jin, Xiaoqing; Si, Caijuan; Huang, Yuan’an; Luo, Zhouxiao; Liu, Tao; Zhu, Jianfang (Frontiers in Physiology, 2021)
Background: This study explored the influences of electroacupuncture combined with dietary intervention on the intestinal flora in perimenopausal patients with abdominal obesity by using the 16s rRNA sequencing technology. Methods: Perimenopausal patients with abdominal obesity were divided into the Electroacupuncture group and the Control group. Patients in the Control group received healthy lifestyle education, while those in the Electroacupuncture group received electroacupuncture combined with dietary intervention. Before and after treatment, the weight, height, waist circumference, hip circumference, waist-height ratio (WHtR), waist to hip ratio (WHR), and body mass index (BMI) of the patients were recorded; the levels of serum triglyceride (TG), total cholesterol (TC), low-density lipoprotein (LDL), high-density lipoprotein cholesterol (HDL-C), fasting insulin (FINS), and fasting blood glucose (FGB) were evaluated; and the abundance, diversity, and species differences of intestinal flora were analyzed using 16s rRNA sequencing technology. Results: The body weight, waist circumference, hip circumference, BMI, WHR, and WHtR of patients in the Electroacupuncture group after treatment were lower than those before treatment. Compared with the Control group, patients in the Electroacupuncture group after treatment displayed lower waist circumference, WHtR, WHR, TG and LDL levels as well as species abundance, higher species diversity, and lager species difference in the intestinal flora. Besides, the proportions of Klebsiella and Kosakonia in the intestinal flora of patients in the Electroacupuncture group after treatment were larger than those before treatment. Conclusion: Electroacupuncture combined with diet treatment generated a therapeutic effect on abdominal obesity in perimenopausal patients by improving the community structure of intestinal flora.